ANALISIS PENGARUH PROFITABILTAS DAN UKURAN PERUSAHAAN TERHADAP STOCK RETURN DENGAN INCOME SMOOTHING SEBAGAI VARIABEL MODERASI - Bernadetta Dian Novita; Abriandi Abriandi (LPMP Imperium, 2019)
This research aimed to determine the effect of the profitability which is measured using Return On Assets (ROA) and Firm Size measured using total assets to stock return with income smoothing as moderating variable. The object in this research is manufacturing companies listed in Indonesian Stock Exchange period 2012-2016. The research using Indeks Eckel as income smoothing indicator. The technique of sampling using purposive sampling so 70 companies have been selected as sample. The multiple linear regression analysis and moderated regression analysis are used as the data analysis , also used t test (partial) and F test (simultaneously) to Goodness of fit test on SPSS 23. The result of this research shows that partially profitability has positive and significant effect to stock return, while firm size has negative and not significant effect to stock return. Simultaneously, profitability and firm size have significant effect to stock return. Income smoothing can not moderate the relationship of profitability and firm size to stock return.